Politics Of Legislation As Socio-Equilibrium In Indonesia - Ismidar Ismidar; Tamaulina Br. Sembiring; Saphta Nugraha Isa (International Journal of Law, Crime and Justice, 2024)
The formation of laws and updates to legal materials must be aimed at realizing social equilibrium , namely an orderly, just and prosperous life. The pattern of communication or dialogue and dialectics that occur in the process of forming legislation will affect the character of the law, the more transparent and participatory the more responsive the law will be. This research method uses normative juridical. The legal policy of legislation should include three things: (i) guarantee justice in society ; (ii) create a peaceful life (create alive placidity ) by maintaining legal certainty; and (iii) realize usefulness (realize use ) by handling real interests in common life in a concrete manner. The application of the principle of justice is based on "legal enforceability" and "equality before the law". The principle of legal certainty is achieved through: (i) clear and firm norming regarding obligations and prohibitions; (ii) legal transparency that prevents society from normative confusion; and (iii) continuity of legal order that provides a reference for future behavior. The principle of utility is based on the ability of law as a social instrument to integrate the aggregation of social interests so that they do not clash with each other, and instead order occurs.